Do manifesto dos 113 à unidade na luta: a trajetória da articulação e os conflitos internos do Partido dos Trabalhadores na construção de uma coalizão dominante (1983-1995) - Ribeiro, Marco Aurélio Santana (Universidade Federal de São Carlos, 2015)
In the last three decades, the Partido dos Trabalhadores (PT) was one of the political parties that most stimulated research in the Brazilian academy. Much has already been spoken of PT. Never has a political party in the history of Brazilian politics presented such a singular trajectory becoming one of the main contenders and organizers of the current Brazilian political system. One novelty brought by PT's party structure is its internal plurality. Composed of various different trends, that shaped and structured themselves across time, PT fostered an intense internal debate regarding these thesis and ideas structured by its several chains of thought. Considered one of its main chains, Articulação was created in 1983 by the Manifesto dos 113. This chain structured itself throughout 1980 being the majority within the party since its birth. This thesis' objective is to investigate the constitution of PT's dominant coalitions and the internal conflicts of its trends resulting from domination attempts over partisan uncertainty areas. The chosen time frame to analyze PT's National Meetings is from 1983 to 1995. The party's electoral performance in São Paulo for congress and state representatives in 1986, 1990, and 1994 will also be examined. This thesis' hypothesis is that the dominant coalition created by Articulação had a strong internal cohesion in the party while constituting it, promoted by it trends' performance within the electoral arena, granting it greater capacity to manage resources from elected offices and, consequently, dominating uncertainty areas within PT.
From the manifesto dos 113 to unidade na luta: the trajectory of articulação and the internal conflicts of the Workers' Party in the construction of a dominant coalition (1983-1995)
Keywords: Organização partidária; Articulação; Democracia intrapartidária; Partido dos Trabalhadores; CIENCIAS HUMANAS::CIENCIA POLITICA::ESTADO E GOVERNO